Hubungan Pengetahuan Dan Sikap Ibu Dengan Kejadian Kekurangan Energi Kronis (KEK) Pada Ibu Hamil Di Wilayah Kerja UPT Puskesmas Kuok - Nuriyah Laila Sari; Fitri Apriyanti; Nia Aprilla (LPPI Yayasan Almahmudi Bin Dahlan, 2025)
Chronic Energy Deficiency (CED) in mothers, especially during pregnancy, has an impact on the health of the mother and baby. In mothers, CED increases the risk of infection, pregnancy complications, anemia, physical weakness, and mental and reproductive health disorders. In infants, maternal CED can cause low birth weight (LBW), stunting, developmental disorders, and the risk of perinatal death. The purpose of this study was to see if there was a relationship between knowledge and attitudes with the incidence of CED in pregnant women in the Kuok Health Center UPT Work Area. This type of research is analytical with a cross-sectional design. The population of this study was all pregnant women in the Kuok Health Center UPT work area totaling 128 people with a sample of 108 people taken using the stratified random sampling technique. The data collection tool in this study used a questionnaire. This study was conducted from 7-21 August 2024. This study used univariate and bivariate analysis. The results of the study showed that most respondents experienced CED, most respondents had less knowledge about balanced nutrition and most respondents had negative attitudes. There is a relationship between maternal knowledge about balanced nutrition and the incidence of KEK in pregnant women with a p value of 0.000. There is a relationship between attitudes and the incidence of KEK in pregnant women with a p value of 0.001. It is expected that health workers can improve counseling on nutrition and motivation for pregnant women to consume nutritious foods to avoid KEK in pregnant women.